Network of Words: A Co-Occurrence Analysis of Nation-Building Terms in the Writings of Liang Qichao and Chen Duxiu - Chao, Anne S.; Liu, Zhandong; Li, Qiwei (Journal of Historical Network Research, 2021)
Liang Qichao (1873-1929) and Chen Duxiu (1879-1942) were two of the most brilliant writers and influential public intellectuals in late nineteenth-, early twentieth-century China. Born six years apart, both men electrified the country with their publications of New Citizen’s Journal and New Youth, respectively, and heralded the character of a new and modern citizen, befitting a new century and a new China. Central to both men’s concerns is the relationship between the citizen and the state. At the end of his checkered political career, Liang concluded that the uninformed Chinese population would best be governed by enlightened autocracy. Chen, after his expulsion from the Chinese Communist Party and alienation from the Chinese Trotskyists, wavered between the dictatorship of the proletariat and democratic socialism. Did both men seemingly opt for an authoritarian rule for China and reject their ideal of liberty and democracy from their younger days? Our paper aims to test this hypothesis that Chen and Liang both saw the need for a centralized power, albeit in different political frameworks, by using quantitative literature analysis. We examined the similarities and differences between their writings on the pairwise co-occurrence of thirty terms related to the topic of nation-building. We created a network with these thirty terms, where an edge between a pair of terms indicates a significant relationship. The relationship is defined as the proportion of writings where both terms co-occurred. The visualization yields information on some preliminary differences in the writings of both men, to be further examined.